(NsO^INENIQ W ^ETYREH TOMAH(B. (NtOM (B4s - Alexander Ivanovich Herzen (Moscow (NpRAWDAs, 1988)
(Nw ^ETWERTYJ TOM (B"(NsOBRANIJ(B" (Na(B. (Ni(B. (NgERCENA (B(1812 - 1870) (NWKL@^ENY BELLETRISTI^ESKIE PROIZWEDENIQ PISATELQ(B, (NSOZDANNYE IM W (B1840 - 1870 (NGODY(B.s
Keywords: Fiction